Transabdominal Migration of Retained Surgical Sponge - Guner, Ali (Hindawi Publishing Corporation, 2012)
Retained surgical sponge (RSS) is a rare surgical complication. The RSSs are mostly located intra-abdominally but they can also be left in the thorax, spine, extremity, cranium, and breast. RSS is often difficult to diagnose because of the nonspecific clinical symptoms and radiologic findings. Clinically, RSS may present as an exudative reaction in the early postoperative period or may also cause an aseptic fibrous tissue response. A foreign body may remain asymptomatically silent for a long time, and it may later present with obstruction, fistulization, or mass formation. In this report, we present a case in which an RSS has migrated through the abdominal wall and caused an anterior abdominal wall abscess.